THE INFLUENCE OF CEO CHARACTERISTICS ON FIRM GROWTH OPPORTUNITIES: EVIDENCE FROM NIGERIAN NON-FINANCIAL FIRMS - L., Alfred (International Journal of Management and Allied Research (IJMAR), 2022)
This study investigates the impact of CEO duality and CEO nationality on growth opportunities of listed firms in emerging African economies, particularly Nigeria. It employs a robust methodology to examine the relationship between CEO duality and growth opportunities and to ascertain the influence of CEO nationality on growth opportunities. The research is guided by agency theory, which explains the principal-agent relationship between shareholders and company executives. The research gap on these topics is addressed to facilitate a better understanding of CEO dynamics from the perspective of emerging economies. Using 76 non-financial firms in Nigeria, data for the study was drawn from company financial statements and the Nigerian Exchange Group database. The study utilizes an ex-post facto quantitative research design due to the longitudinal secondary data utilized. The results show that CEO duality has no significant relationship with firms’ growth opportunities, however, CEO nationality has a significant influence on growth opportunities. Specifically, CEO nationality is positively associated with firm growth opportunities. The research findings contribute to the literature on CEO dynamics and its implications on corporate governance and succession planning in the context of the Nigerian economic landscape.